2021
DOI: 10.1093/cvr/cvab299
|View full text |Cite
|
Sign up to set email alerts
|

The adult heart requires baseline expression of the transcription factor Hand2 to withstand right ventricular pressure overload

Abstract: Aims Research on the pathophysiology of right ventricular (RV) failure has, in spite of the associated high mortality and morbidity, lagged behind compared to the left ventricle (LV). Previous work from our lab revealed that the embryonic basic helix-loop-helix transcription factor heart and neural crest derivatives expressed-2 (Hand2) is re-expressed in the adult heart and activates a ‘fetal gene program’ contributing to pathological cardiac remodeling under conditions of L… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 60 publications
0
5
0
Order By: Relevance
“…There it is induced by upstream progesterone (P4)-Indian hedgehog (IHH) signaling during menstrual cycles and initiates downstream MET (also termed decidualization 59 )-a key requirement for blastocyst receptivity during implantation 60 . In wider adult-tissue pathological contexts (type 2/3 MET), however, HAND2 is associated with endometriosis induction (upregulating proinflammatory IL15 expression 61,62 ), right ventricle protection from pressure overload damage 26 , familial dilated cardiomyopathy 63 , onset of mesothelioma malignancies 30 and obesity (regulated by glucocorticoid signaling) 64 . HAND2 is also silenced in colorectal cancer (via hypermethylation correlated with poor prognosis) and has been identified as an epigenetic driver gene and a potential tumor suppressor (via MAPK/ERK signaling) 65 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There it is induced by upstream progesterone (P4)-Indian hedgehog (IHH) signaling during menstrual cycles and initiates downstream MET (also termed decidualization 59 )-a key requirement for blastocyst receptivity during implantation 60 . In wider adult-tissue pathological contexts (type 2/3 MET), however, HAND2 is associated with endometriosis induction (upregulating proinflammatory IL15 expression 61,62 ), right ventricle protection from pressure overload damage 26 , familial dilated cardiomyopathy 63 , onset of mesothelioma malignancies 30 and obesity (regulated by glucocorticoid signaling) 64 . HAND2 is also silenced in colorectal cancer (via hypermethylation correlated with poor prognosis) and has been identified as an epigenetic driver gene and a potential tumor suppressor (via MAPK/ERK signaling) 65 .…”
Section: Discussionmentioning
confidence: 99%
“…One possible downstream common mediator of MET may be heart and neural crest derivatives 2 (HAND2), a type B basic helix-loop-helix (bHLH) transcription factor (TF) 24 , and its associated anti sense long non-coding RNA (lncRNA, HAND2-AS1). Embryonically, HAND2 induces type 1 (embryonic) MET patterning of NCCs to branching aortic vessels and of mesodermal second heart field (SHF) cells to the right ventricle (RV), parts of the atria, interventricular septum, and outflow tract [25][26][27] . HAND2 murine knockout (KO) is lethal at E9.5-10.5, yielding RV hypoplasia, single chambered hearts, and vascular malformations 25,28 .…”
Section: Introductionmentioning
confidence: 99%
“…At this level, it is induced by upstream progesterone (P4)-Indian hedgehog (IHH) signaling during menstrual cycles and initiates a downstream MET (also termed decidualization [57])-a key requirement for blastocyst receptivity during implantation [58]. In wider adult tissue pathological contexts (type 2/3 MET), however, HAND2 is associated with endometriosis induction (upregulating proinflammatory IL15 expression [59,60]), right ventricle protection from pressure overload damage [26], familial dilated cardiomyopathy [61], the onset of mesothelioma malignancies [30], and obesity (regulated by glucocorticoid signaling) [62]. HAND2 is also silenced in colorectal cancer (via hypermethylation correlated with poor prognosis) and has been identified as an epigenetic driver gene and a potential tumor suppressor (via MAPK/ERK signaling) [63].…”
Section: Discussionmentioning
confidence: 99%
“…One possible downstream common mediator of MET may be heart and neural crest derivatives 2 (HAND2), a type B basic helix-loop-helix (bHLH) transcription factor (TF) [24], and its associated antisense long non-coding RNA (lncRNA; HAND2-AS1). Embryonically, HAND2 induces type 1 (embryonic) MET patterning of NCCs to branching aortic vessels and of mesodermal second heart field (SHF) cells to the right ventricle (RV), parts of the atria, interventricular septum, and outflow tract [25][26][27]. HAND2 murine knockout (KO) is lethal at ED9.5-10.5, yielding RV hypoplasia, single-chambered hearts, and vascular malformations [25,28].…”
Section: Introductionmentioning
confidence: 99%
“…Its regulatory targets have been found to control mesenchymal transition underlying cardiac cushion development in the atrioventricular canal [12]. A recent study found that a baseline expression of the gene in the adult heart is required to withstand right ventricular pressure overload [13]. Variation of the ZNF385D gene (rs13070110) was nominally associated with an increased risk of intracerebral hemorrhage [14].…”
Section: Introductionmentioning
confidence: 99%